Engineering Advanced In Vitro Models of Systemic Sclerosis for Drug Discovery and Development. Issue 4 (15th February 2021) - De Pieri, Andrea; Korman, Benjamin D.; Jüngel, Astrid; Wuertz‐Kozak, Karin
Abstract: Systemic sclerosis (SSc) is a complex multisystem disease with the highest case‐specific mortality among all autoimmune rheumatic diseases, yet without any available curative therapy. Therefore, the development of novel therapeutic antifibrotic strategies that effectively decrease skin and organ fibrosis is needed. Existing animal models are cost‐intensive, laborious and do not recapitulate the full spectrum of the disease and thus commonly fail to predict human efficacy. Advanced in vitro models, which closely mimic critical aspects of the pathology, have emerged as valuable platforms to investigate novel pharmaceutical therapies for the treatment of SSc. This review focuses on recent advancements in the development of SSc in vitro models, sheds light onto biological (e.g., growth factors, cytokines, coculture systems), biochemical (e.g., hypoxia, reactive oxygen species) and biophysical (e.g., stiffness, topography, dimensionality) cues that have been utilized for the in vitro recapitulation of the SSc microenvironment, and highlights future perspectives for effective drug discovery and validation. Abstract : Systemic sclerosis (SSc) is a complex disease with the highest case‐specific mortality among autoimmune rheumatic diseases, yet without any available curative therapy. Advanced in vitro models have emerged as valuable platforms for drug discovery and screening. This review focuses on recent advancements in the development of SSc in vitro models and highlights future perspectives for effective drug development and validation.